JARIMAH QADZAF (TUDUHAN ZINA) DALAM PERSPEKTIF HUKUM PIDANA ISLAM: IMPLIKASI TERHADAP HAK ASASI MANUSIA - Dhimas, Muhammad; Dzakwan Mtd, Mhd Daffa; Dalimunthe , Nadya Rahma; Nabila Siregar , Annisa Sasa; Aisywani, Meutia; Handayani, Mira; Yusuf Hamdani, Ahmad (Gapenas Publisher, 2025)
The crime of qadzaf, as a criminal act of accusing someone of adultery without valid evidence according to Islamic law, has significant implications for the protection of human rights (HAM). The enforcement of qadzaf law aims to protect personal honor, dignity, and social stability from the threat of baseless accusations. This article discusses the crime of qadzaf as a form of protection of the right to honor, the right to a sense of security, and the right to a peaceful life, as guaranteed in international law, especially Article 12 of the Universal Declaration of Human Rights and Article 14 paragraph (2) of the International Covenant on Civil and Political Rights. Although the law of qadzaf is often seen as restricting freedom of opinion, its basic principle actually balances the right to expression with the social responsibility to protect the honor of others. With a philosophical approach based on maqashid sharia, this article emphasizes that the application of the law of qadzaf is a preventive and restorative legal mechanism that remains relevant in guaranteeing human rights in the contemporary era.